The Nature of Knowledge in the Context of Islamic Educational Philosophy - Ahmad Fauzan; Maspuroh; Fahir Ali; Tia Esapitri; Yopa Nurlaela (Penerbit Hellow Pustaka, 2025)
This article discusses the nature of science in the context of Islamic educational philosophy using the literature method. Science is not only understood as a collection of facts, but as a process that involves the mind, heart and senses. Through a critical approach, this research identifies sources of knowledge which include insaniyah, qauliyah, and kauniyah verses in achieving the ultimate goal of the search for marifatullah knowledge or knowledge about Allah.